The Missing Mummy - Roy, Ron 1940-; Gurney, John (New York : Random House, 2001)
Dink, Josh, and Ruth Rose help catch the thieves who have stolen the treasure from the museum's mummy exhibit.
"A stepping stone book."
"Grades 2-4"--cover p. [4].
Keywords: Mystery and detective stories; Stealing -- Fiction